COMPUTER ANXIETY DAN KEAHLIAN END USER COMPUTING DALAM PENGGUNAAN TEKNOLOGI INFORMASI - Rustiana Rustiana (KINERJA, 2005)
In the digital era, one of negatif impact is computer anxiety. But, one of the future trend in information technology is the increase end user capabilities to use and interact with the computer. In the other words there will be a decrease in computer anxiety and an increase in capabilities to use the computer. Capabilities to use the computeris as well as a proxy in computer self efficacy. The purpose of the studi is to investigate the effect about of computer anxiety on computer self efficacy end users computing. Questionaire has distributed to 149 management information system as a respondent. Data was analysed by dimple regression and the result supported the hipotesis. Implication of the study is to improve the computer learning to process of computer of the student.Keywords: computer anxiety, computer self efficacy, end user computing